Development of Website Public Complaint System Polibatam V2.0 - Nasrullah, Muchamad Fajri Amirul; Sinarti, Sinarti; Santiputri, Metta; Manurung, Vicky Leonardo (JISA(Jurnal Informatika dan Sains), 2022)
The development of technology at this time, every agency certainly tries to improve the quality of its services. The Complaint Application is an information system that aims to provide aspirations for the performance of an agency. In this case the researchers took the case of the Batam State Polytechnic, where the campus wanted to realize Bureaucratic Reform at the Batam State Polytechnic by making a website-based Polibatam Complaint Application. Initially, the website was completed in the fourth semester during the implementation of Project Based Learning. In this case, the researcher conducted research to create a V.0 Complaints application with improvements from a website that had been built previously so that a website-based Public Complaint Application design was needed that was easy to use and could see responses to aspirations and complaints. The method that the researcher uses in designing the Polibatam V2.0 Complaint Application is the Waterfall model with MySql as the Database Management System, as well as PHP, JavaScript as the programming language to be used and Laravel as the PHP Framework. The completed application is then tested using the black box testing methodology, which allows all functionalities to be executed and implemented in accordance with the previously created functional requirements